Hypothermic Storage of Human Hepatocytes for Transplantation. Issue 9 (September 2014) - Gramignoli, Roberto; Dorko, Kenneth; Tahan, Veysel; Skvorak, Kristen J.; Ellis, Ewa; Jorns, Carl; Ericzon, Bo-Goran; Fox, Ira J.; Strom, Stephen C.
Transplantation of human hepatocytes is gaining recognition as a bridge or an alternative to orthotopic liver transplantation for patients with acute liver failure and genetic defects. Since most patients require multiple cell infusions over an extended period of time, we investigated hepatic functions in cells maintained in University of Wisconsin solution at 4°C up to 72 h. Eleven different assessments of hepatic viability and function were investigated both pre- and posthypothermic storage, including plating efficiency, caspase-3/7 activity, ammonia metabolism, and drug-metabolizing capacity of isolated hepatocytes. Long-term function, basal, and induced cytochrome P450 activities were measured after exposure to prototypical inducing agents. Cells from 47 different human liver specimens were analyzed. Viability significantly decreased in cells cold stored in UW solution, while apoptosis level and plating efficiency were not significantly different from fresh cells. Luminescent and fluorescent methods assessed phases I and II activities both pre- and post-24-72 h of cold preservation. A robust induction (up to 200-fold) of phase I enzymes was observed in cultured cells. Phase II and ammonia metabolism remained stable during hypothermic storage, although the inductive effect of culture on each metabolic activity was eventually lost. Using techniques that characterize 11 measurements of hepatic viability and function from plating efficiency, to ammonia metabolism, to phases I and II drug metabolism, it was determined that while viability decreased, the remaining viable cells in cold-stored suspensions retained critical hepatic functions for up to 48 h at levels not significantly different from those observed in freshly isolated cells.